1997
DOI: 10.1148/radiology.205.1.9314987
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral washout sign on contrast-enhanced MR images of the breast.

Abstract: Peripheral washout may be a reliable sign of malignancy on delayed contrast-enhanced MR images of the breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 0 publications
3
51
1
2
Order By: Relevance
“…In IBC, however, wash-out time curves prevail, mainly based on persistent neovascularisation. The wash-out phenomenon of invasive carcinomas is supposed to be caused by arteriovenous anastomoses with a consequent fast contrast medium outflow and the large number of capillaries with a high blood flow rate, resulting in a rapid transport of contrast agent from the intravascular to the interstitial compartment [14,15]. This mechanism also can explain the blooming sign [23] which was significantly more frequent in patients with IBC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In IBC, however, wash-out time curves prevail, mainly based on persistent neovascularisation. The wash-out phenomenon of invasive carcinomas is supposed to be caused by arteriovenous anastomoses with a consequent fast contrast medium outflow and the large number of capillaries with a high blood flow rate, resulting in a rapid transport of contrast agent from the intravascular to the interstitial compartment [14,15]. This mechanism also can explain the blooming sign [23] which was significantly more frequent in patients with IBC.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is up-regulated in malignant as well as inflammatory processes and is supposed to act as a key cytokine in breast oedema because of its influence on neovascularisation and increased permeability of these new capillaries [30,31,32]. Furthermore, blood vessels observed in carcinomas and inflammatory reactions typically show vasodilatation, which also results in oedema [15,30,31]. The distinct oedema is particularly responsible for the characteristic enlargement of the affected breast [8,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type II (plateau curve) and type III (washout curve) are suggestive for malignancy, but the latter is highly predictive of malignant disease. Washout phenomenon alone has a positive predictive value of 87% [5], and peripheral washout is to 100% associated with breast cancer [47]. Both type-II and type-III curves have maximal uptake in the early postcontrast phase, but this qualitative criterion includes no subcategories according to the onset of contrast uptake.…”
Section: Mr Enhancement Kineticsmentioning
confidence: 99%
“…Delayed-phase scans were acquired at 4 min after the start of intravenous administration of the contrast material, whereas in Kitagawa's study, 19 the corresponding scans were obtained at 10 min after injection of the contrast material. Sherif's group 24 reported that a characteristic steep decline of the enhancement curve between 4 min and 10 min is observed at the periphery of the tumor in cases of breast carcinoma. Thus, rim enhancement detected in the early phase may remain in delayedphase scans acquired at 4 min after the injection of contrast material (Fig.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%